The Emergence of the Semen Between Backbone and the Ribs: Review of the Scholars’ Interpretation of Surah At-Tariq Verse 7 - Muhammad Naim Rosli; Ahmad Bazli Ahmad Hilmi; Amir Mustaqim Mohd Naim; Lana Arash Qurnia Hairul Nizam; Daniel Fandi Ngieng (Kolej PERMATA Insan, 2024)
4th Insan Junior Researchers International Conference 2023 (iJURECON 2023) : "STREAM for a better future”/ editors : Ahmad Fuad Mohamad Amin, Nurhidaya Mohamad Jan, Nur Aisyah Mohamed, Nur Fatin Fathillah Mazlan 27-28 October 2023 Organized by : Kolej Permata Insan